Implementation of Educational Supervision Management in Improving Teachers' Performance in Secondary Schools - Irda Suriani; Nur Halima Astia; Desi Andini Siregar; Aqila Zahra; Fadhila Rifda Siregar; Siti Rahma Siregar; Fatimah Azzarah; Aqila Aqila; Nopia Ramadani Tanjung; Alya Syahfitri (Literasi Nusantara, 2026)
This study aims to examine the implementation of educational supervision management in improving teachers’ performance in secondary schools. The research employs a qualitative descriptive approach through observations, interviews, and document analysis involving school principals, supervisors, and teachers. The findings indicate that effective supervision management contributes significantly to enhancing teachers’ professional competence, instructional quality, classroom management, and commitment to continuous professional development. The implementation of systematic supervision, including planning, classroom observation, constructive feedback, and follow-up evaluation, encourages teachers to improve their teaching practices and achieve better educational outcomes. However, several challenges remain, such as limited supervisory time, administrative workload, and varying levels of teacher readiness. The study concludes that effective educational supervision management is a strategic approach to improving teachers’ performance and supporting sustainable school quality improvement. Strengthening collaboration among school leaders, supervisors, and teachers is essential for maximizing the effectiveness of supervision practices